AN ANALYSIS OF DIRECTIVE SPEECH ACTS IN “CINDERELLA” MOVIE - Lee, Suryanti; Afriana, Afriana (SCIENTIA JOURNAL, 2020)
It is a common phenomenon for people in using pragmatics in their daily communication. People tend to express themselves implicitly with intention which is discussed in illocutionary acts. The intention are such as commanding, informing, expressing themselves and so on. Illocutionary acts that was developed by Searle (1976) has five types, representative/(assertive), directive, commissive, expressive and declaration. One of the types that often be used is directive which is classified into few classes such as command, beg, advise and request. This research was aimed to analyzed the classes and the frequency of directive speech acts that are uttered by the characters in”Cinderella” movie. This research was analyzed by applying descriptive qualitative method which is explained in words, phrases and sentences. The data will be collected from the characters’ utterance in “Cinderella” movie. The researcher used observational method, non-participatory and note taking technique method in collecting the data. The result of this research showed that the characters in “Cinderella” movie used all classes of directive speech acts. The most frequently used is command which had 36 data (69,2%) meanwhile the least used is request which had only 1 data (1,9%).